Solubility factors as screening tools of biodegradable toughening agents of polylactide. Issue 48 (11th June 2015) - Ruellan, Alexandre; Guinault, Alain; Sollogoub, Cyrille; Ducruet, Violette; Domenek, Sandra; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT Changes in the thermomechanical properties of polylactide (PLA) plasticized by two biodegradable and biobased molecules, Polysorb ID37 (PID37) and squalene, were compared to formulations with petroleum‐based plasticizers, namely, acetyl tributyl citrate, poly(ethylene glycol) 400, and dioctyl adipate (DOA). The solubility parameters of the additives were calculated and were related to the plasticization behaviors. PID37 proved to be miscible with PLA because of its polar functions and short alkyl groups. It decreased the PLA glass‐transition temperature (Tg) and increased in ductility when Tg approached room temperature. Squalene had a low miscibility because of the absence of polar groups. Tg was not depressed. Ductility improvements were nevertheless reached because the immiscible inclusions efficiently induced crazing by the distribution of stress concentration points all over the material; this delayed failure. The maximum elongations at break were 60% for squalene, 400% for DOA, and 500% for PID37. The solubility factors were, thus, an efficient prediction tool for the plasticizing behavior. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42476.